Toni Morrison's The Bluest Eye: When Beaaty Turns Out To Be Hegenomy - Trisnawati, Ririn Kurnia (Journal of English and Education (JEE), 2008)
The United States of America is a race-conscious society that those who are colored (as opposed to white) have generally been put in inferior positions and treated accordingly. Consequently, apparently White Anglo Saxon Protestants (WAPS)has been inherently put as the dominant group whereas the African American is consciously placed as one of the subordinate ones. Theory of hegemony proposed by Antonio Gramscihas been believed as a means to understand the position of the superior and the inferior groups in the society. Meanwhile, the concept of beauty is an example of cultural institution; hence, the standard of beauty is based on the dominant group e.g. White people, so there is the White beauty standard as a means of hegemonic practice in the American society. This phenomenon is thoughtfully depicted by Toni Morrison in The Bluest Eye. Therefore, this writing aims at describing the phenomena when beauty turns out to be the hegemonic practice of White beauty standard in African American society as it is depicted in Toni Morrison's The Bluest Eye.lhc study shows that White beauty standard has been the hegemonic practice that is consciously alive in the African Americans as the society members involved in the story. The hegemony itself is from the beauty standards which are standardized using the White people's beauty standards e.g. light skinned, blue eyes, blonde, slimmer body image, etc. The White beauty standard hegemony is not solely the single reason of maintaining domination and power; in fact, society members, and their will and consciousness have also participated in it. Therefore, the implications occur within the society under the hegemonic practices or the hegemonized society, so do the characters in this novel. Those implications are extracted from the characters living in the novel as the characters are the hegemonized subject in practice. It is the fact that White beauty standard hegemony has led to the emergence of intra-racial discrimination happening within the African American society as it is reflected in the literary work due to the characters' efforts to seek for White's approval. The second is the emergence of the self-loathing upon the characters in the novel, and the third is the emergence of the self identity degrading.